DAMPAK VIDEO YOUTUBE DALAM PEMBELAJARAN TEKS CERITA INSPIRATIF - Endina Alya Iskandar; Dida Firmansyah (Parole : Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2022)
This research is motivated by the fact that the lack of students' writing skills is especially difficult in expressing ideas, ideas and messages in their writings. In this study, the researcher chose an inspirational story text as the topic of discussion. The purpose of this research is to train students to be able to compose inspirational story texts according to the structure and rules of the language. So that students can compose inspirational story texts here using youtube videos in learning inspirational story texts, it is hoped that the youtube videos will make it easier for students to write inspiring story texts and be able to reflect on their ideas and ideas. Another purpose of this study is to determine the impact for students of using YouTube videos on learning inspirational story texts. Researchers use qualitative methods as an analysis that will disassemble the findings with a dividing instrument. The results of the study prove that students are better able to express ideas because they are the result of inspiring videos on YouTube and provide an active atmosphere in the learning process.